An innovative concrete-steel structural system for long-span structure allowing a fast and simple erection. (October 2019) - Lepourry, Clemence; Heng, Piseth; Somja, Hugues; Boissonnade, Nicolas; Palas, Franck
Abstract: In achieving medium-to-long span slab, steel-concrete composite beams may offer an alternative over pre-stressed beams for the so-called disadvantages of the latter; for example the heavy weight of pre-stressed beams makes their handling expansive. However, the use of composite beams by concrete builders is still limited due to the lack of specific tools and skills for on-site erections and the need for a supplementary fire protection. This article presents an innovative steel-concrete moment resisting portal frame that overcomes these difficulties. It is composed of composite tubular columns, and a composite beam made of a U-shape steel profile used as permanent formwork to encase a concrete beam. The steel-concrete duality of the proposed beam allows an erection on site without any weld or bolt by a wise positioning of the construction joints. As only steel elements have to be handled on site, there is no need of heavy cranes. This system has been used to build a research center near Rennes, in France. As it is not covered in present norms, an experimental validation was required. In this paper, a series of full-scale experimental tests that have been performed in order to assess the global and the local behaviour of the frame and its connections are presented. A series of asymmetrical push-out tests were carried out in order to determine the ductility and resistance of shear connectors; one 4-point bending test was made to investigate the resistance under sagging bending moment; and, two tests of the beam-to-column joint were performed in order to validate a strut and tie design model of the joint. Finite element simulations have also been made in order to acquire more information for the development of the analytical models.